Standard functional solution within the framework of multinationality - عبد, مصطفى سالم; فانوس, حوراء قاسم (Journal of Legal Sciences, 2021)
One of the most significant difficulties raised by the phenomenon of multiple nationalities is the designation of the law applicable to the dispute involving a foreign element in which the rules of attribution refer to the application of personal law in matters of personal status, which has resulted in jurisprudence and jurisprudence in this area to several criteria that can be applied to weighting one of the nationalities held by the foreign national, as well as the position of national legislation that adopted the most likely of these standards, It can be embodied in two traditional directions represented by the standards of the judge 's law and the law of actual nationality, while the modern trend is the criterion of functional solution.